Quantitative analysis of the economic flows between Portugal and the other European Union member states and institutions in 1997 - Santos, Susana (2013)
In a “top-down” approach, for which the starting point should be the building of an aggregated Social Accounting Matrix (SAM) based on the country’s national accounts statistics, a SAM will be built for the Portuguese economy in 1997. The SAM will be shown as a work instrument for quantifying the flows in the economic circuit and for simulating resulting effects of changes in such flows. The full consonance with the National Accounting System will be demonstrated identifying the identities and balances of the various internal accounts of the System in the constructed SAM. The economic flows between Portugal and the other European Union Member States and Institutions will be emphasised and the accounting multipliers that are calculated will facilitate the study of the resulting effects of changes in these flows. The impact of a total cut in investment grants from the European Union to the Portuguese economy will be studied.